The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/evj.12013
|View full text |Cite
|
Sign up to set email alerts
|

Expression of anti‐Müllerian hormone, CDKN1B, connexin 43, androgen receptor and steroidogenic enzymes in the equine cryptorchid testis

Abstract: This study provides a better understanding of the effect of cryptorchidism on testicular function in stallions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 48 publications
0
15
1
Order By: Relevance
“…Unilateral cryptorchidism in animals occurs significantly more often than bilateral cryptorchidism (1). The left cryptorchid testis in dogs is usually located in the abdominal cavity, while the right cryptorchid testis can be found in the inguinal canal (1). The cases of cryptorchidism in European bison recorded in our study deviated from this rule, since both left and right cryptorchid testes were found in the inguinal canal.…”
Section: Resultscontrasting
confidence: 66%
See 1 more Smart Citation
“…Unilateral cryptorchidism in animals occurs significantly more often than bilateral cryptorchidism (1). The left cryptorchid testis in dogs is usually located in the abdominal cavity, while the right cryptorchid testis can be found in the inguinal canal (1). The cases of cryptorchidism in European bison recorded in our study deviated from this rule, since both left and right cryptorchid testes were found in the inguinal canal.…”
Section: Resultscontrasting
confidence: 66%
“…The normal development of the gubernaculum is Cryptorchidism can be unilateral or bilateral (30). Unilateral cryptorchidism in animals occurs significantly more often than bilateral cryptorchidism (1). The left cryptorchid testis in dogs is usually located in the abdominal cavity, while the right cryptorchid testis can be found in the inguinal canal (1).…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the effects of retention on testicular development is thus crucial when attempting to give evidence-based advice about whether a testicle that finally descends into the scrotum in a 2-to 3-year-old colt still has the capacity to develop into a grossly normal testicle. This explains the value of the report by Almeida et al [1] that the retained testicles from 2-to 3-year-old cryptorchids maintain the molecular characteristics of prepubertal testes. This suggests that retention leads to a delay in development without, at least during the first 3 years, loss of the potential to develop spermatogenetic capacity if and when relocated to a suitable environment, i.e.…”
mentioning
confidence: 72%
“…This explains the value of the report by Almeida et al . that the retained testicles from 2‐ to 3‐year‐old cryptorchids maintain the molecular characteristics of prepubertal testes. This suggests that retention leads to a delay in development without, at least during the first 3 years, loss of the potential to develop spermatogenetic capacity if and when relocated to a suitable environment, i.e.…”
mentioning
confidence: 93%
See 1 more Smart Citation